Aid effectiveness and selectivity: Integrating multiple objectives into aid allocations - Mark McGillivray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper surveys recent research on aid and growth. It also provides an overview of research on inter-recipient aid allocation. The overall focus of the paper is on the relevance of these issues for poverty-efficient aid, defined as a pattern of inter-recipient aid allocation which maximises poverty reduction. It identifies a range of povertyreducing criteria on which aid allocation or selectivity might be based, calling for a broader selectivity framework. The paper argues that this framework should be built on a recognition that the effectiveness of aid in increasing growth, and by implication in reducing poverty, is contingent on a range of factors in addition to the quality of recipient country policy regimes. These factors include political stability, democracy, post conflict reconstruction, and economic vulnerability.
Keywords: F35; E61; I31; I32; O19; H53; 330; aid; growth; policy; selectivity; poverty reduction; post-conflict; democracy; political stability; economic vulnerability; Entwicklungshilfe; Armutspolitik; Wirtschaftswachstum